Amputee Sports for Victims of Terrorism - Centre of Excellence Defence Against Terrorism, Turkey Ankara (IOS Press, 2013)
Sir Ludwig Guttmann organized a sports competition in 1948 which became known as the Stoke Mandeville Games, involving World War II veterans. In 1952 competitors from the Netherlands took part. The first Olympic-style games for athletes with a disability was in Rome in 1960, and since 1988 the Paralympics have been held in conjunction with the Olympics (1992 for the Winter Olympics). There are various categories of disability recognised by the Paralympic Committee. Since the 2000 Sydney Games the intellectual disabilities category has been suspended. There are currently twenty paralympic sports, and six winter paralympic sports. In 2000 Turkey sent an athlete for the first time, and the Turkish National Paralympic Committee was formed in 2002. At present amputee football is not recognised as a paralympic sport.